Generalized boundary values of solutions of quasilinear elliptic equations with linear principal part - Lopushanskaya, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We establish conditions for the nonlinear part of a quasilinear elliptic equation of order $2m$ with linear principal part under which a solution regular inside a domain and belonging to a certain weighted $L_1$-space takes boundary values in the space of generalized functions.